>>>>> "Pyotr" == Pyotr Ivanshin <pivanshin at gmail.com> writes:
Pyotr> The output of this program is simply wrong.
Pyotr> f[0](z,t):=rw5*z^k+rw5*t^k;
Pyotr> S:"ddc";
Pyotr> M[0]:5;
Pyotr> for j:1 thru slength(S) step 1 do (if charat(S, j)="a" then
Pyotr> (M[j]:M[j-1]-2, h[j](z,t):=(M[j]
Pyotr> +1)*(M[j]+2)*integrate(f[j-1](z,t), t)/2, f[j](z,
Pyotr> t):=-(1/4)*integrate(h[j](z, t)
Pyotr> -h[j](t,
Pyotr> z), z))
Pyotr> elseif charat(S, j)="b" then (M[j]:M[j-1]-2, h[j](z,t):=Mu*(M[j]
Pyotr> +1)*(M[j]+2)*integrate(f[j-1](z,t), t)/2, f[j](z, t):=(h[j](z,t)+h[j](t,z))/2)
Pyotr> elseif charat(S, j)="c" then (M[j]:M[j-1]-1, f[j](z,
Pyotr> t):=(-1/2)*(M[j]+1)*integrate(f[j
Pyotr> -1](z,t), z))
Pyotr> elseif charat(S, j)="d" then (M[j]:M[j-1]-2, f[j](z,
Pyotr> t):=-(M[j]+1)*(M[j]+2)*integrate(integrate(f[j
Pyotr> -1](z,t), z), t))
Pyotr> elseif charat(S, j)="e" then (M[j]:M[j-1]-1, f[j](z,
Pyotr> t):=-Mu*(M[j]+1)*f[j-1](z, t))
Pyotr> elseif charat(S, j)="f" then (M[j]:M[j-1]-1, f[j](z,
Pyotr> t):=(M[j]+1)*integrate(integrate(f[j
Pyotr> -1](z,t), z), t)/Mu)
Pyotr> );
Pyotr> Even f[1] (z, t) equals wrong expression.
Pyotr> Would anybody be so kind as to show me my mistake?
It would probably a lot more helpful if you actually explained what
this is computing and what the expected answer should be and why you
think it's wrong.
Ray, who didn't even try the code :-(